Blepharophimosis Ptosis Epicanthus Inversus Syndrome (BPES) Type 1 in an Indian Family - Gupta, Abhinav Kumar; Gupta, Deepak Chand; Khan, Saqib Ahmad; Razi, Syed Mohd (Journal of the ASEAN Federation of Endocrine Societies, 2017)
Blepharophimosis ptosis epicanthus inversus (BPES) is a relatively rare congenital disorder, which usually presents with classical eye manifestations. In some cases, it is associated with premature ovarian failure (POF). BPES is of two types, type I and type II. Type I is associated with POF along with eyelid malformations, while Type 2 has only eyelid malformations. Here, we report a family of BPES, in whom two sisters presented with secondary amenorrhea. On eye examination, they have blepharophimosis, ptosis, epicanthus inversus and telecanthus. Investigations revealed hypergonadotropic hypogonadism. Their father also has similar eye manifestations. Diagnosis of BPES type I was made and both were started on hormone replacement therapy. To make timely diagnosis of BPES, every patient with POF should specifically be checked for eye manifestations.